KIDNEY MORPHOLOGY OF FEMALE KINTAMANI DOG - Putra, I Kadek Pradhana; Heryani, Luh Gde Sri Surya; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2020)
Kintamani dog is a local mountain type dog that lives in Sukawana Village, Kintamani District, Bangli Regency, Bali. Research on the urinary system in Kintamani dog has never been done. This study aims to determine the morphology of anatomy and morphometrics of the kidney (ren) in Kintamani dog macroscopically and microscopically. This study used the kidney of 5 Kintamani dogs with an average age of 1-2 years old originating from the village of Sukawana. Histological observation based on Kiernan method and Hematoxylin-eosin (HE) staining. Weight measurement data, length, width, and renal thickness data were analyzed using Independent Sample T-test to compare the left and right kidney. Meanwhile, the anatomical and histological structure of the kidneys were analyzed descriptively qualitatively. The results showed that the left and right kidney weight was significantly different (P <0.05), while the length, width, and thickness were not significantly different (P> 0.05). Measurements of right renal morphometry, weight: 19.39 ± 4.24 g; length: 50.19 ± 2,43 mm; width: 29.57 ± 1.94 mm; cortex thickness: 6.17 ± 0.45 mm; medulla thickness: 8.48 ± 0.56 mm and pelvis thickness: 8.11 ± 1.29 mm. While the left kidney, weight: 20.51 ± 4.20 g; length: 50.88 ± 2,38 mm; width: 29.40 ± 1.65 mm; cortex thickness: 6.17 ± 0.31 mm; medulla thickness: 8.50 ± 0.49 mm and pelvis thickness: 8.95 ± 2.08 mm. Results of renal histomorphometry measurements, capsula thickness: 37.18 ± 5,67 mm; glomerulus area: 8.598,34 ± 1.277,06 mm; cortex thickness: 3.798,34 ± 603,54 mm and medulla thickness: 1.485,09 ± 286,92 mm.